2022
DOI: 10.3390/cancers14020384
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Endometrial Cancer Using Fusion T2-Weighted Images with Diffusion-Weighted Images: A Way to Avoid Gadolinium?

Abstract: Endometrial cancer is the eighth most common cancer worldwide, and its prognosis depends on various factors, with myometrial invasion having a major impact on prognosis. Optimizing MRI protocols is essential, and it would be useful to improve the diagnostic accuracy without the need for other sequences. We conducted a retrospective, single-center study, which included a total of 87 patients with surgically confirmed primary endometrial cancer, and who had undergone a pre-operative pelvic MRI. All exams were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Nevertheless, they obtained higher diagnostic accuracies. Neves et al (2022) [20] had a sample of 87 patients and revealed a statistically significantly higher capacity of fused images to evaluate the degree of myometrial invasion compared to standard MRI evaluation with T2WI, DWI, and DCE sequences. Mongula et al (2019) [21] found that fusion of T2W with DWI showed a significant increase in diagnostic performance for the assessment of parametrial invasion in early-stage cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they obtained higher diagnostic accuracies. Neves et al (2022) [20] had a sample of 87 patients and revealed a statistically significantly higher capacity of fused images to evaluate the degree of myometrial invasion compared to standard MRI evaluation with T2WI, DWI, and DCE sequences. Mongula et al (2019) [21] found that fusion of T2W with DWI showed a significant increase in diagnostic performance for the assessment of parametrial invasion in early-stage cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Image fusion technique can fuse two groups of different images at the same location to achieve complementary advantages, which is conducive to the diagnosis and evaluation of diseases. A study of endometrial cancer showed that the image fusion technique based on T2WI and DWI could improve the diagnostic accuracy, sensitivity, and speci city of the depth of myometrium invasion [14]. In a CMR study, Okune et al [15] found that the fusion image analysis of 18 F-uorodeoxyglucose positron emission tomography and LGE improved the diagnostic agreement and accuracy of cardiac sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies demonstrated the image fusion technique can combine the two different images to improve the diagnostic accuracy for diseases [14,15]. This technique can retain the advantages of two images simultaneously through post-processing, without the need for additional image scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high DWI signal of endometrial cancer and hypointensity of adjacent myometrium, DWI has also been useful for accurate determination of the depth of myometrial invasion [ 1 ]. The combined use of T2-weighted and DWI images increases the sensitivity for accurately detecting myometrial invasion from endometrial cancer [ 38 ]. DWI improves the sensitivity of detection of metastatic lymph nodes by using the size and ADC values in conjunction, and it is comparable to dynamic contrast-enhanced MRI for detecting nodal metastasis from endometrial cancer in some studies and [ 39 , 40 ].…”
Section: Clinical Applications In Gynecological Malignanciesmentioning
confidence: 99%